Tablets as a digital tool in supervision of student teachers' practical training - Petter Mathisen; Cato Bjørndal (Universitetsforlaget, 2016)
In the project "Tablets in Practicum Supervision", the tablet has been tested as a tool for observation and supervision in Norwegian teacher education. The study incorporates 14 practicum supervision groups and focuses on how the use of tablets can influence the quality of the supervision and the coherence between teaching, observation and supervision. Throughout the supervision process, the groups have used tablets to produce and share texts, pictures and video recordings. The use of tablets has resulted in eight aspects of quality improvement: improved observations, stronger motivation, improved feedback, increased sharing of opinions, improved coherence, improved structure, improved preparations, and increased reflection.